Media Influence of Planting And Concentration of Organic Liquid Fertilizer on The Growth And Results Lettuce (Lactucasatival.) - Sri Purwanti; Bambang Gunawan; Ari Yulianto (Agricultural Science, 2018)
The lettuce is a leafy vegetable that comes from the (state) temperate. Historically, this plant has been cultivated since 2500 years ago. Lettuce plants came from the Americas. This is evidenced by Christopher Columbus in 1493 that found the plant lettuce in the western Hemisphere and the Bahamas (Rukmana, 1994). This study aims to determine the effect of growing media on growth factors, the influence of the concentration of liquid organic fertilizer (POC), the interaction effect of these two factors and yield of lettuce. The results showed There is a very real effect of growing media composition in all parameters studied were long observation of plants, number of leaves and fresh weight per plant. The best results were achieved by treatment K2 is 2 kg of manure per plant. There is a very real effect of concentrated liquid fertilizer (POC) "Supermer" on all parameters studied were long observation of plants, number of leaves and fresh weight per plant. The best results are achieved by P4 treatment The concentration POC 2 ml / liter of water. There is no real interaction due to a combination treatment of the media composition and concentration of liquid organic fertilizer (POC) "Supermes".